How I Braved Anu Aunty & Co-Founded a Million Dollar Company - Agarwal. Varun (Bengaluru: Rupa Publications, 2012)
How does an unfocused young person such as Varun Agarwal, become the co-founder of a million dollar company? How does he get pesky Anu Aunty off his trail? The book How I Braved Anu Aunty & Co-Founded A Million Dollar Company is an interesting real-life story of how the author, Varun Agarwal, managed to brave all odds to reach the peak of his career.Varun Agarwal is shown to be an unfocused human being, with no real interest in pursuing a career, even though he does harbour dreams of becoming a successful entrepreneur. Varun whiles away his time, hopping from pub to pub, spending time with friends and keeping a track of his love interest on Facebook.These traits worry his mother to the bone, compelling her to put the very meddlesome Anu Aunty on the job, to help get her son moving in the right direction in life. Anu Aunty does a rather good job of this, much to Varun's dismay. He then does all that he can to get her off his track, while pursuing his dreams to become an entrepreneur.Published on 1st April, 2012, How I Braved Anu Aunty & Co-Founded A Million Dollar Company can be purchased in paperback. What is most interesting about this story is the beautiful portrayal of the author's real-life struggle and success in the entrepreneurial world. Key Features The book gives you a relatable real-life account of the author's sojourn in the corporate world and in life as well. The writing-style employed by the author can be easily comprehended by anyone, especially youngsters.